Pendampingan Pelaporan SPT Tahunan Dengan Menggunakan Aplikasi E-Filling Melalui Program Relawan Pajak - Waly, Nur Aeni; Bintari, Wisang Candra; Wangsi, Mitta Muthia; Lestari, Bekti Wiji; Wijiastuti, Retno Dewi; Andjar, Febri Jein; Jamil, Ahmad; Prihandoko, Nugroho Dwi; Sari, Rosita Firda (Jurnal Dehasen Untuk Negeri, 2025)
The problem of plastic waste in urban areas such as Jakarta continues to increase along with Taxation is a vital primary source of state revenue essential for national development. To support the improvement of taxpayer compliance, the Indonesian government has implemented a self-assessment system and utilized e-Filing technology for the Annual Tax Return reporting. However, the level of public literacy and understanding of taxation and the use of e-Filing remains low. This article discusses the implementation of the 2024 Tax Volunteer Program involving students from Muhammadiyah University of Sorong as assistants in the Annual Tax Return reporting at KPP Pratama Sorong. The methods employed include intensive preparation, training, and direct assistance to taxpayers. The results indicate that the assistance provided by tax volunteers effectively enhances taxpayers’ understanding and compliance, as well as facilitates the SPT reporting process through e-Filing. Challenges such as limited infrastructure and tax literacy are still encountered; however, overall, this program contributes positively to fostering a culture of tax reporting within the community.